2016
DOI: 10.3389/fpsyg.2016.00579
|View full text |Cite
|
Sign up to set email alerts
|

Harm Avoidance and Self-Directedness Characterize Fibromyalgic Patients and the Symptom Severity

Abstract: Objective: Evidence in the literature suggests peculiar personality traits for fibromyalgic (FM) patients, and it has been suggested that personality characteristics may be involved in patients’ different symptomatic events and responses to treatment. The aim of the study is to investigate the personality characteristics of Italian FM patients and to explore the possibility of clustering them considering both personality traits and clinical characteristics.Design: The study used a cross-sectional methodology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
4
7
0
Order By: Relevance
“…They were as high as healthy controls in the character traits of SD and CO, and in the temperament trait of PS, and as low in the temperament trait of HA ( Cloninger & Zohar, 2011 ). This result is very similar to that of Leombruni et al (2016) who also found two distinct personality clusters for FM patients, with the bigger cluster characterized by resilient personality profile and emotional style. The first group of patients was the mal-adapted cluster, characterized by higher levels of HA and alexithymia, higher frequency of type D, and lower levels of CO, SD, PS, RD positivity and social support.…”
Section: Discussionsupporting
confidence: 87%
“…They were as high as healthy controls in the character traits of SD and CO, and in the temperament trait of PS, and as low in the temperament trait of HA ( Cloninger & Zohar, 2011 ). This result is very similar to that of Leombruni et al (2016) who also found two distinct personality clusters for FM patients, with the bigger cluster characterized by resilient personality profile and emotional style. The first group of patients was the mal-adapted cluster, characterized by higher levels of HA and alexithymia, higher frequency of type D, and lower levels of CO, SD, PS, RD positivity and social support.…”
Section: Discussionsupporting
confidence: 87%
“…Manuscript to be reviewed They were as high as healthy controls in the character traits of SD and CO, and in the temperament trait of PS, and as low in the temperament trait of HA. This result is very similar to that of Leombruni et al (Leombruni et al 2016) who also found two distinct personality clusters for FM patients, with the bigger cluster characterized by resilient personality profile and emotional style. The first group of patients was the mal-adapted cluster, characterized by higher levels of HA and alexithymia, higher frequency of type D, and lower levels of CO, SD, PS, RD positivity and social support.…”
Section: Personality Evaluationsupporting
confidence: 87%
“…Individuals in this cluster had a frequency of type D personality which was similar to the general population; high as healthy controls in the character traits of SD and CO, and in the temperament trait of PS, and as low in the temperament trait of HA. (Cloninger & Zohar 2011) This result is very similar to that ofLeombruni et al (Leombruni et al 2016) who also found two distinct personality clusters for FM patients, with the bigger cluster characterized by resilient personality profile and emotional style. The first group of patients was the mal-adapted cluster, characterized by higher levels of HA and alexithymia, higher frequency of type D, and lower levels of CO, SD, PS, RD positivity and social support.…”
supporting
confidence: 76%